1998
DOI: 10.1007/s003300050372
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography versus computed tomography in evaluation of the femoral trochlear groove morphology: a pilot study on healthy, young volunteers

Abstract: The aim of the study was to verify the efficacy of ultrasonography (US) in evaluating the morphology of normal trochlea, especially the sulcus angle and the trochlear depth, in comparison with computed tomography (CT) (gold standard). The knees of 11 asymptomatic volunteers were subjected to US and CT evaluation of the same section planes and the results were compared. For statistical evaluation Spearman's correlation coefficient analysis was used. A statistically significant correlation was found between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…However, their measurements were based on the borders of the trochlear bone. Furthermore, the measurements were made in 90° knee flexion using the tangential to the upper patellar bone as a reference point to identify the axial cut for measurements [8]. This might explain the difference to our measurements, where we found a mean trochlear depth of 4.2 mm in men.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, their measurements were based on the borders of the trochlear bone. Furthermore, the measurements were made in 90° knee flexion using the tangential to the upper patellar bone as a reference point to identify the axial cut for measurements [8]. This might explain the difference to our measurements, where we found a mean trochlear depth of 4.2 mm in men.…”
Section: Discussionmentioning
confidence: 81%
“…Secondary outcomes were the size of the lateral and medial trochlear groove facets and their ratio. Sample size calculation was based on the study of Martino F. et al [8], who measured trochlear depth on axial CT images (Table 2: CT measurements of the trochlear depth, first series). For a 95 % CI with an error of ±1 mm [95 % CI = mean ± 1.96*(SD/Hn)], sample size was three patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of 2015 (Fischoff C.) found that only one diagnostic study published by Lapègue et al [ 18 ] showed a relatively simple protocol used in current practice for MRI evaluation; it is performed by US based on three diagnostic criteria (cartilaginous trochlear angle, PTTG distance, and the presence or absence of dysplasia). Moreover, quantitative and qualitative US criteria have been validated [ 17 , 18 ]. However, further research on the reliability of US tests for these criteria is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) allows for the evaluation of the peripatellar soft tissues and the trochlear cavity cartilage, as well as its relationship with the patellar tip. Quantitative and qualitative US criteria have been approved as an important tool in any diagnostic testing [ 16 , 17 ], but the reliability of their inter-operator measurements has never been studied. Compared to most radiological techniques, in which images are acquired using predefined protocols, US image acquisition is more complex and operator-dependent [ 18 ].…”
Section: Introductionmentioning
confidence: 99%